Internationalisation strategies of born-digitals from emerging countries: Cases from Indonesia - Dharwiyanti, Sri; Djajadikerta, Hamfri; Sulungbudi, B. Meylianti (Edelweiss Applied Science and Technology, 2026)
Indonesian born-digital firms face unique challenges such as limited resources and a lack of international reputation. The majority of them do not act as born-global companies. Indonesian digital companies had only begun to consider internationalisation in the last decade. The research addresses how Indonesian born-digitals navigate challenges to expand globally and compares the strategy with international business theory, utilizing multiple case studies of ten Indonesian born-digital firms. Data were collected through in-depth interviews and document analysis, focusing on understanding the strategic decisions made by these companies. Many born-digital companies follow the Uppsala model, gradually expanding after establishing a strong domestic presence. Key strategies include leveraging local and technology partnerships and selecting the right destination country and market segment. The study also highlights the importance of balancing product replication with modification and accelerating internationalisation with the role of third-party funding. The empirical findings build propositions that enhance the understanding of internationalisation processes in emerging markets and extend international business theories. As practical implications, this research provides insights for leaders of born-digital firms in emerging markets into formulating effective internationalisation strategies by evaluating competencies, networks, and competitive advantages.